The Monitoring Reliability Analysis And Excessive Electricity Use Protection With OCR And Atmega 16 - Muhammad Angga Dwi Andika; Solly Aryza; Zuraidah Tharo (Jurnal Scientia, 2024)
One of the disturbances that occur in the electrical network is short circuit disturbances. This interference can be overcome by using an OCR/GFR relay that works with circuit breaker equipment. However, if the relay experiences problems, then when a short circuit occurs in the network, the relay cannot work to secure the installation, and will cause an expansion of the affected outage area. At the Sei Rotan Bay Power Transformer Substation 3, there was a case of sympathetic tripping caused by the OCR/GFR Brand Micom P142 relay on the ST4 feeder experiencing an error and not being detected by the working operator due to the absence of an indication of the error relay, and the result was disruption to the feeder. This caused the Power Transformer Incoming Bay 3 to go out. For this reason, it is necessary to install an unhealthy relay condition monitoring circuit in the cubicle and protection panel. Experiments on installing the unhealthy relay monitoring circuit were carried out in the ST5 spare cubicle. Installing a monitoring circuit in the ST5 spare cubicle can work well by providing a visual indication in the form of an error relay indication light, and also an audible indication in the form of a buzzer which can be heard in the operator's room. Apart from that, installing the unhealthy relay monitoring circuit does not cause problems with the 110 VDC working system in the ST5 cubicle.